Shareholder personal risk and firm risk: An empirical analysis of share pledges and firm debt policies - Xia, Jiahui; Wu, Zhanchi; Zhang, Rongwu; Chen, Xiangyi; Zhang, Rui (Frontiers in Psychology, 2022)
The impact of personal risk caused by controlling shareholders’ equity pledges on the company’s debt policy is an issue worth exploring. Using Chinese A-share listed companies from 2006 to 2020, this paper studies the impact of ultimate owner equity pledges on firm debt size and debt maturity structure and explores the mechanism of ultimate owner personal leverage on firms. The results show that the increase in ultimate owner stock pledges leads to higher financial leverage and longer debt maturity structure of the company. In addition, the study reveals that high personal leverage of the ultimate owner of the pledged equity is an influential mechanism driving the transfer of personal risk to the firm. In particular, even if a company’s actual debt ratio is higher than its target debt ratio, equity pledges can prompt listed companies to increase their debt ratios and debt maturities, causing them to take on excessive debt risk and transferring the risk to creditors. It follows that the tunneling effect as a driving force of equity pledging and corporate debt policies. These results remain robust after robustness test and endogenous test. The conclusions of this paper not only emphasize the impact of shareholders’ personal risk on the firm, but also provide a reference for investors’ perception of firm risk.